Variation of Resurrection Duration Using 0,50% NaOCl Solution on Delignification of Mahoni Wood Powder Waste (Swietenia Macrophylla King.) - Yusuf, Yusnidar; Hariyanti; Albayas, Hasbi (International Journal of Psychosocial Rehabilitation, 2020)
Cellulose is one source of the synthesis of ethanol contained in various plants, including mahogany. In the synthesis of ethanol from plants, delignification process is required to degrade lignin that binds the cellulose in this wood. This research conducted to determine the optimal conditions delignification of mahogany. The studies initiated by smoothing wood, then sieved using a sieve mesh no. 60 for similarity of size and increase the surface area. It followed by soaking the powder using a saline solution of 0.50% NaOCl as delignification within 27, 28, 29, 30, 31 and 32 hours. Then it followed by extraction of mahogany extractive substances using benzene and ethanol with soxhlet extractor method, and followed by testing lignin with Klason method through H2SO4 with principle cellulose hydrolysis using sawdust in order to obtain residual lignin deposition. The results showed the most optimal time delignification process was 30 hours of immersion that is a decrease of 10.05% lignin degradation with the highest rise as much as 0.20%.